Strategi Seniman Kaligrafi Dalam Mengikuti Lomba Hiasan Mushaf di Kota Palangka Raya - Asep Solikhin; Nuraida Rahmi (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
Calligraphy or commonly known as khath is one of Islamic art which received great attention from the Muslim community, not least the Muslims in the city of Palangkaraya. In fact, the calligraphy is used as one of the branches that are contested in Musabaqah Tilawatil Qur'an (MTQ), namely Musabaqah Khattil Qur'an (MKQ). In MKQ divided into three (3) groups: group branches manuscript, ornamentations and decor. The ability of the artists of calligraphy in making ornamentations at the time of the race, would have a different strategy with the aim that the resulting work better and can be categorized as the best. Subject (source data) in this study consists of three (3) artists, calligraphy, calligraphic artist group three are ornamentations with a proven record in the race making ornamentations. The results showed that: first, the most supportive factor in implementing strategies make decorations Manuscripts at the time of the race, there are two (2) factors: (a) Factors Psychic (Soul), which strengthen the spiritual self to God; (B) Physical factors (Physical), ie prior to the start of the race and to consume nutritious foods and regular breaks; second, the difficulties encountered in making the calligraphy artist ornamentations at the time of the race was the lack of preparation, drafting difficulties paragraph, and difficulties in the manufacture of trim and motifs.